Pengaruh Return on Asset (ROA) dan Debt to Equity Ratio (DER) Terhadap Price to Book Value (PBV) Pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2022 - Purnomo, Albert Kurniawan; Kartika Sari, Utari; Nuralizah, Arnetta (Owner : Riset dan Jurnal Akuntansi, 2024)
Company value is one of the important elements that need to be maximized for the prosperity of shareholders so that shareholders can invest their capital in the company. The purpose of this study was to measure and analyze the effect of Return On Asset (ROA) and Debt to Equity Ratio (DER) on Price to Book Value (PBV) in Food and Beverage Sub-Sector companies listed on the Indonesia Stock Exchange. This study uses associative methods that are quantitative data. The analytical method used is descriptive test, classical assumption test, multiple linear regression analysis, t test, F test and the coefficient of determination. The data used is secondary data obtained by 13 companies in the published annual reports. Based on the results of the study, it shows that the Return On Asset (ROA) and Debt to Equity Ratio (DER) variables have a partial effect on Price to Book Value (PBV). Variables Return On Assets (ROA) and Debt to Equity Ratio (DER) have an effect on Price to Book Value (PBV) simultaneously.